Characterizing pinprick-evoked brain potentials before and after experimentally induced secondary hyperalgesia - van den Broeke, Emanuel N. (J Neurophysiol, 2015)
Secondary hyperalgesia is believed to be a key feature of “central sensitization” and is characterized by enhanced pain to mechanical nociceptive stimuli. The aim of the present study was to characterize, using EEG, the effects of pinprick stimulation intensity on the magnitude of pinprick-elicited brain potentials [event-related potentials (ERPs)] before and after secondary hyperalgesia induced by intradermal capsaicin in humans. Pinprick-elicited ERPs and pinprick-evoked pain ratings were recorded in 19 healthy volunteers, with mechanical pinprick stimuli of varying intensities (0.25-mm probe applied with a force extending between 16 and 512 mN). The recordings were performed before (T0) and 30 min after (T1) intradermal capsaicin injection. The contralateral noninjected arm served as control. ERPs elicited by stimulation of untreated skin were characterized by 1) an early-latency negative-positive complex peaking between 120 and 250 ms after stimulus onset (N120-P240) and maximal at the vertex and 2) a long-lasting positive wave peaking 400–600 ms after stimulus onset and maximal more posterior (P500), which was correlated to perceived pinprick pain. After capsaicin injection, pinprick stimuli were perceived as more intense in the area of secondary hyperalgesia and this effect was stronger for lower compared with higher stimulus intensities. In addition, there was an enhancement of the P500 elicited by stimuli of intermediate intensity, which was significant for 64 mN. The other components of the ERPs were unaffected by capsaicin. Our results suggest that the increase in P500 magnitude after capsaicin is mediated by facilitated mechanical nociceptive pathways.